Optimalisasi Perkembangan Motorik Kasar Pada Anak Melalui Permainan Tradisional Egrang Tempurung Kelapa - Hasna, Saffanatun; Susanti, Lizza (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
The existence of this research is motivated by the lack of proficiency in early childhood in recognizing and sorting numbers. An effort that can be done is to use a smart board. This use is intended to help facilitate early childhood in improving their cognitive abilities. This study aims to help children aged in the development of cognitive skills through the method of matching numbers on a smart board. This study uses a qualitative method in a descriptive way. The results of the study show that the smart board method can help children to optimize their cognitive skills, the achievement of this method is quite good. The results of this study can be used as an alternative to the selection of models in the development of children's cognitive abilities about numbers.